Pain experience and satisfaction with postoperative pain control among surgical patients. Issue 3 (30th October 2014) - Subramanian, Pathmawathi; Ramasamy, Suguna; Ng, Kwan Hoong; Chinna, Karuthan; Rosli, Roshaslina
Abstract : Alleviating acute pain and providing pain relief are central to caring for surgical patients as pain can lead to many adverse medical consequences. This study aimed to explore patients' experience of pain and satisfaction with postoperative pain control. A cross‐sectional survey was carried out among 107 respondents who had undergone abdominal surgery in the surgical ward of an urban hospital using the Revised American Pain Society's Patient Outcome and Satisfaction Survey Questionnaires (APS‐POQ‐R). Data were analysed using descriptive statistics and chi‐square test. Chi‐square test showed significant association between race ( P = 0.038), education level ( P ≤ 0.001), previous operation status ( P = 0.032) and operation status ( P ≤ 0.001). Further analysis on nominal regression, association between dissatisfaction with factors of operation status (46.09 (95% CI 7.456, 284.947)) and previous operation status (13.38 (95% CI 1.39, 128.74)) was found to be significant. Moderate to high levels of pain intensity in the last 24 h after surgery, as well as moderate to high rates of pain‐related interference with care activities were most reported. Pain still remains an issue among surgical patients, and effective pain management and health education are needed to manage pain more effectively after surgery.